Repercussions of mild diabetes on pregnancy in Wistar rats and on the fetal development - Saito, Felipe H. [UNESP]; Damasceno, Débora Cristina [UNESP]; Kempinas, Wilma G. [UNESP]; Morceli, Glilciane [UNESP]; Sinzato, Yuri K. [UNESP]; Taylor, Kristin N. [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Biomed Central Ltd., 2010)
Background: Experimental models are necessary to elucidate diabetes pathophysiological mechanisms not yet understood in humans. Objective: To evaluate the repercussions of the mild diabetes, considering two methodologies, on the pregnancy of Wistar rats and on the development of their offspring.Methods: In the 1st induction, female offspring were distributed into two experimental groups: Group streptozotocin (STZ, n = 67): received the beta-cytotoxic agent (100 mg STZ/kg body weight - sc) on the 1st day of the life; and Nondiabetic Group (ND, n = 14): received the vehicle in a similar time period. In the adult life, the animals were mated. After a positive diagnosis of pregnancy (0), female rats from group STZ presenting with lower glycemia than 120 mg/dL received more 20 mg STZ/kg (ip) at day 7 of pregnancy (2nd induction). The female rats with glycemia higher than 120 mg/dL were discarded because they reproduced results already found in the literature. In the mornings of days 0, 7, 14 and 21 of the pregnancy glycemia was determined. At day 21 of pregnancy (at term), the female rats were anesthetized and killed for maternal reproductive performance and fetal development analysis. The data were analyzed using Student-Newman-Keuls, Chi-square and Zero-inflated Poisson (ZIP) Tests (p < 0.05).Results: STZ rats presented increased rates of pre (STZ = 22.0%; ND = 5.1%) and post-implantation losses (STZ = 26.1%; ND = 5.7%), reduced rates of fetuses with appropriate weight for gestational age (STZ = 66%; ND = 93%) and reduced degree of development (ossification sites).Conclusion: Mild diabetes led a negative impact on maternal reproductive performance and caused intrauterine growth restriction and impaired fetal development.